PRINSIP MEMBERIKAN KEMUDAHAN DAN MENYENANGKAN DALAM PROSES PENDIDIKAN (Suatu Tinjauan dalam Perspektif Hadits) - Asmuri Darma (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
The development and progress of the times marked by the advancement of science and technology implications for the structure and mechanism of human life in all lines and dimensions. This fact as well as a challenge, especially in the administration and management of education, including Islamic education. Islamic education is required to transform both institutional and individual, especially for teachers as an important actor in the world of education. The teachers are required to make changes with regard to the approach, strategy and methods applied in the learning activities. There were many theories and learning approaches offered by educational experts. Among them is a fun approach to learning. Truly a fun learning approach in the perspective of Islamic education is not a new thing. But already there and has been practiced since the time of the beginning of Islamic education. As illustrated by the hadith of the Prophet SAW stated;